Utilization of Medicinal Plants in Turi Putih Village, Blitar, East Java and Antibacterial Tests against Staphylococcus aureus and Escherichia coli - Sri Endarti Rahayu; Dini Wulan Dari; Yulneriwarni Yulneriwarni (Journal of Tropical Biodiversity, 2021)
Plants contain compounds that can be considered as antimicrobials. The community of Turi Putih Village have used plants that have medicinal properties to treat certain diseases, especially those caused by bacteria. For this reason, it is necessary to conduct research on the use of medicinal plants and antibacterial tests from plants originating from Turi Putih Village. The purpose of this study was to determine the diversity of medicinal plants, plant parts used, preparation and use of medicinal plants by the local community, as well as the antibacterial potential of medicinal plants that have High score of Use Value (UV) and Fidelity Level (FL) ​​to treat those diseases. Data was collected by using semi-structural interviews and respondents were chosen by purposive sampling. To analyze the data, we adopted qualitative and quantitative ethnobotanical technique. Qualitative, namely descriptive methods to make an inventory of the composition of medicinal plants and preparation and use by the community, and quantitative to see the most commonly used and most preferred species ethnomedicinal plant species for treating certain ailments. . Based on interviews with respondents, the community uses 44 species of medicinal plants, 40 genus that belong to 26 plant families to treat 19 diseases caused by bacteria. Based on UV and FL scores, mint leaves (Mentha piperita) and kencur leaves (Kaempferia galanga) had the highest scores. The results showed that mint leaves and kencur leaves have antibacterial activity by forming an inhibition zone against Staphylococcus aureus and Escherichia coli. In this study, extract from leaf of K. galanga appeared to be more potent than that of leaf of M. piperita, and produced consistent level of inhibition of bacterial growth. Since it was revealed that the leaves extract of Kaempferia galanga has the ability to inhibit the growth of Staphylococcus aureus – food – poisoning organism, hence, it would be interesting to investigate the potentially of this plant for possible application in foods to promote safety.